Biochemical Indicators of nutritional status and dietary intake in Costa Rican Cabécar Indian Adolescents - Monge Rojas, Rafael (2005)
The purpose of this study was to determine the blood levels of selected nutritional status indicators and the dietary intake of Costa Rican Cabécar Indians aged 10 to 16 years. The results showed that 65% of the adolescents had an adequate body mass index (BMI) for their age, and 32% had a BMI < 5th percentile. Likewise, the study revealed a high prevalence of anemia (57%), deficient serum folate levels (54%), deficient vitamin B12 levels (31%), and subclinical vitamin A deficiency (10%). Additionally, the youngsters had elevated prevalences of high triglyceride levels (77%), borderline high-density lipoprotein (HDL) cholesterol levels (46%), homocysteine levels > 10 µmol/L (29%), and homozygous mutation of methylenetetrahydrofolate reductase (MTHFR) (49%). The diet was poor, being high in saturated fat and low in polyunsaturated fat, fiber, and several micronutrients. The dietary intakes of more than 55% of the adolescents did not meet 50% of the estimated average requirements (EAR) for zinc, vitamin A, vitamin C, vitamin B12, vitamin B2, and folate. Furthermore, a high prevalence of parasitosis was found (68%). Our results show an adolescent Cabécar population with a mosaic of nutritional deficiencies and cardiovascular risk factors.